Implementasi dan Pengembangan Program Humas Melalui Integrasi Articial Intelligence di Lembaga Pendidikan Islam Tingkat Pesantren dan Perguruan Tinggi - Maizah, St.; Saputra, Mohammad Irsyad Wira; Abidin, Zeinal (re-JIEM (Research Journal of Islamic Education Management), 2026)
This study discusses the implementation and development of Public Relations programs in Islamic educational institutions, particularly at the Islamic boarding school (pesantren) and university levels. Public Relations plays a role as a strategy to strengthen public relations, build a positive image of the institution, and serve as an effective means of communication between the institution and the public. The research method used is qualitative with a library research approach, which aims to examine public relations theories, concepts, and practices based on previous research and relevant literature. The results of the study indicate that Public Relations in Islamic boarding schools is oriented towards the values ​​of akhlaqul karimah (good character), da'wah (Islamic outreach), and social community involvement. Meanwhile, Public Relations in universities places more emphasis on the digitalization of communication, professionalism, and transparency. The main obstacles faced by both include a lack of understanding among leaders regarding the importance of Public Relations' role in institutional governance, limited human resources, and limited budgets. Therefore, it is necessary to strengthen Public Relations capacity based on digital technology integrated with Islamic values ​​to be able to meet the challenges of modern communication and maintain the credibility of Islamic educational institutions in the global era.